Microscopic polyangiitis diagnosed by muscle specimen: a case report and literature review. Issue 2 (3rd July 2018) - Murata, Okinori; Izumi, Keisuke; Kaneko, Yuko; Yasuoka, Hidekata; Suzuki, Katsuya; Matsubara, Shiro; Yamaoka, Kunihiro; Takeuchi, Tsutomu
Abstract: We describe the case of a 76-year-old man with microscopic polyangiitis (MPA) presenting with myalgia, abnormal muscle MRI findings and pulmonary fibrosis. Although he had been initially suspected of polymyositis, laboratory tests of normal myogenic enzymes and positive myeloperoxidase-antineutrophil cytoplasmic antibody (MPO-ANCA) and muscle specimen showing vasculitis without myogenic changes led to the diagnosis of MPA. This case indicates that ANCA-associated vasculitis is an important differential diagnosis in patients with muscle involvement and interstitial lung disease.